Opini Remaja terhadap Album Jazz Pop (Studi terhadap Komunitas Penggemar Album Manusia dari Tulus) - Fahrul Wibowo, Okta; Loisa, Riris (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2024)
Tulus is one of the Indonesian singers who is currently successful in performing jazz-pop songs. This study was raised because communication through song lyrics has an influence on young people who listen to jazz-pop music. This research seeks to understand and examine the views of Indonesian youth towards the pop jazz genre, especially in Tulus' album,